Geomorphological analysis of the morphometric properties of Harba basin: (Duhok governorate) - Abdul Sattar Jabir, Ahmed (Al-Adab Journal, 2020)
Morphometric analysis of river basins, its efficiency depends on the accuracy of the used data and the method of analysis. The Harbah basin located in northern Iraq (Dohuk - Aqrah) was chosen as one of the small basins with an area of about (184.80) km2, the aim of this current study is to analyze the morphometric measurements in the Harpah basin By adopting the accuracy of the spatial distinction of the digital height model (30) meters (SRTM- DEM), by adopting the geographic information systems technology and its modifications in the field of morphometric analysis represented by the morphometric toolbox, in order to find out the most important morphometric parameters and their impact on development and planning in the region, the results of the study showed that The basin is ranked sixth according to the Strahler classification, and most of the secondary basins are either of the third or fourth rank, and the direction of flow from the north and northwest towards the south and southeast is in line with the slope of the region and the direction of the folds, and the basin is dominated by the lengthening of valleys because most of its area is 60% a slight slope The morphometric coefficients of the basin indicate the youth of the basin, the beginning of maturity, the dominance of solid rocks, and the weakness of the sedimentary product of the basin other than the molar areas. With a high slope in the north and southwest of the basin, as well as the convergence of secondary basins in most of their morphometric characteristics, for the similarity of the natural components in the region, with concentrations of areas of water concentration in the regions of the north of the basin due to the large numbers of river ranks (first and second) and the area where valleys meet in the middle of the basin. The expansion direction of the basin was south and southeast, due to its connection with the slope and topography of the area.